Association of blood pressure components with mortality and cardiovascular events in prehypertensive individuals: a nationwide population-based cohort study. (4th July 2018) - Oh, Hyung Jung; Lee, Seulbi; Lee, Eun-Kyung; Lee, Oesook; Ha, Eunhee; Park, Eun-Mi; Kim, Seung-Jung; Kang, Duk-Hee; Choi, Kyu Bok; Kim, Seung Jun; Ryu, Dong-Ryeol
Abstract: Background: The effects of each blood pressure index [systolic and diastolic blood pressure (SBP, DBP), pulse pressure (PP), mean arterial pressure (MAP)] on the occurrence of mortality and cardiovascular (CV) events have not yet been investigated in prehypertensive populations. Methods: A total of 30, 258 prehypertensive Korean participants underwent periodic health examination between 2003 and 2004 were enrolled, and the associations of BP components with mortality and CV events were investigated. Moreover, based on the DBP [80 ≤ DBP <90 mmHg ( N  = 21, 323) and DBP <80 mmHg ( N  = 8, 935)], the effects of BP components were also evaluated. Results: Multivariate Cox analyses in prehypertensive group revealed that the hazard ratios (HRs) were 1.121 and 1.130 per 10 mmHg increase in SBP and PP for mortality, respectively. Additionally, 10 mmHg increase of SBP (HR:1.090) was still significantly, but increase of PP (HR:1.060) was marginally associated with higher incidence of CV events. However, there were no significant associations with increase in DBP or MAP on adverse clinical outcomes in prehypertensive group. In the prehypertensive subjects with DBP <80 mmHg, CV events more frequently occurred by 38.8% and 28.5% per 10 mmHg increase in SBP and PP, respectively. Conclusions: Prehypertensive subjects might need to be cautioned when they have high SBP or PP with low DBP even in healthy populations. Key message: Prehypertensive subjects should be cautioned when they have high-systolic blood pressure or pulse pressure with low-diastolic blood pressure, even without previous hypertension, diabetes mellitus or chronic kidney disease.